The Influence of Risk, Leverage, Board Gender Diversity, Moderated by Firm Size on Profitability of Banking Sector - Winiadi, Nicky; Usman, Bahtiar; Nalurita, Febria (Universitas Medan Area, 2024)
The economic growth has been propelled by substantial changes in the monetary framework, the relaxation of financial limitations, and the incorporation into the international market. Various factors influence how companies operate to gain profits. The theory underpinning this research is risk management theory, focusing on how credit risk and market risk affect company profitability. Credit risk refers to potential losses from parties failing to meet their financial obligations, while market risk relates to asset value fluctuations due to market factors. Leverage (debt usage) represents financial theory innovation, addressing how a company's capital structure impacts profitability. Board diversity represents corporate governance theory innovation, examining the influence of female board representation on profitability. This study aims to determine the influence of credit risk, market risk, leverage, and board gender diversity on profitability, considering the moderating effects of business size. The data employed in this study was acquired from the annual financial reports of banking firms listed on the Indonesia Stock Exchange (IDX), covering the period from 2018 to 2023. Purposive sampling identified a sample of 38 banks. The results show that credit risk and market risk significantly positively influence profitability. Credit risk and market risk moderated by firm size significantly negatively affect profitability. Leverage significantly negatively influences profitability, moderated by firm size. Board gender diversity does not affect profitability, and its moderation by firm size also does not affect profitability. Leverage, credit risk, and market risk have the potential to enhance profitability and attract investors, who can consider these factors for better risk-based investment decisions